Pengaruh Sosial Media Dalam Meningkatkan Ekonomi Umkm Kota Medan Di Masa Pandemi Covid-19 (Studi Kasus di Kecamatan Medan Kota) - Aisyah Damayanti; Zulkifli Siregar; Milla Naeruz (Universitas Islam Sumatera Utara, 2022)
In the concept of digital marketing, keeping up with technological developments is considered important in improving the economy of MSMEs (Micro, Small and Medium Enterprises). Relationship variables consisting of social media (X1), unemployment (X2), and changes in consumer behavior (X3) are factors that are considered to affect the economy of MSMEs in Medan Kota District. This quantitative study aims to determine the effect between variables. A total of 101 respondents from MSMEs in Medan Kota District were collected and recorded and then processed using the PLS (Partial Least Square) approach using the SmartPLS software. The results show that social media, unemployment, changes in consumer behavior affect and play an important role in MSMEs